2004
DOI: 10.1021/ic049765o
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dissolution of Copper and Zinc Metal in Carbon Dioxide with tert-Butyl Peracetate and a β-Diketone Chelating Agent

Abstract: A series of beta-diketone ligands, R(1)COCH(2)COR(2) [tmhdH (R(1) = R(2) = C(CH(3))(3)); tfacH (R(1) = CF(3); R(2) = CH(3)); hfacH (R(1) = R(2) = CF(3))], in combination with tert-butyl peracetate (t-BuPA), have been investigated as etchant solutions for dissolution of copper metal into carbon dioxide solvent. Copper removal in CO(2) increases in the order tfacH < tmhdH < hfacH. A study of the reactions of the hfacH/t-BuPA etchant solution with metallic copper and zinc was conducted in three solvents: scCO(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…By dissolution of metals, tert -butyl peracetate was decomposed to tert -butyl alcohol and acetic acid. 133 The oxidative dissolution rate of copper was increased as the alkyl chain length in R 2 DTC – increased or as fluorine substitution was introduced for both the R 4 BAE and R 2 DTC – ligands. The Li(R 2 DTC) salts were more effective in copper removal than Na(R 2 DTC).…”
Section: Other Oxidizing Agentsmentioning
confidence: 99%
“…By dissolution of metals, tert -butyl peracetate was decomposed to tert -butyl alcohol and acetic acid. 133 The oxidative dissolution rate of copper was increased as the alkyl chain length in R 2 DTC – increased or as fluorine substitution was introduced for both the R 4 BAE and R 2 DTC – ligands. The Li(R 2 DTC) salts were more effective in copper removal than Na(R 2 DTC).…”
Section: Other Oxidizing Agentsmentioning
confidence: 99%
“…For each tin centre, three of the Sn-O bonds are shorter with the distances ranging from 2.083 3 however, a comparison of Cu-O distances reveals that one of the bonds is more than 0.01 Å shorter [1.914 (3) Å ] in the unsolvated species. Elongation of Cu-O bonds is generally observed in Cu II -diketonates upon coordination of O-donor ligands (Xu et al, 2000;Maverick et al, 2002;Visintin et al, 2005;Pampaloni et al, 2005;Filyakova et al, 2009;Pointillart et al, 2010) in comparison with unsolvated species. In most cases, the effect is more pronounced than is observed in (I).…”
Section: Figurementioning
confidence: 99%
“…This study showed that over a 20-hour period, a significant amount of copper could be removed. Several other studies were also quickly published that demonstrated various chelating agents and oxidants can remove copper from surfaces in CO 2 in a fairly reliable manner [2,[8][9][10][11]. Some studies also included the use of surfactants and cosolvents to help improve the removal of copper [12].…”
Section: Introductionmentioning
confidence: 99%